Improving The Function of The Prabu Geusan Ulun Museum in Sumedang Regency as A Tourist Attraction for Historical and Cultural Education - Deni Hermawan; Maylan Sofian; Kuswara Kuswara (PANGGUNG, 2017)
The museum of Prabu Geusan Ulun Sumedang has been in existence since 1950. How- ever, its existence has not been recognized widely among members of society, including among Sumedang community. To solve the problem, it is important to do some e?orts for improving the a#raction of the museum by increasing its functions, not only as a place of storing ancient objects, but also as a tourist destination for history and cultural educations. To obtain this goal, a qualitative research has been conducted, in which its collecting data was undertaken directly in the ?eld by observations, interviews, and documentation with a digital camera. From the research, it can be concluded that improving the functions of the Prabu Geusan Ulun museum as a tourist atraction is need to be done by developing the supporting system of the museum. These include providing several media such as booklets and website, making labels for the museum objects, and developing museum activities. All of these activities lead to the ability of the museum as a tourist destination of history and culture educations. Keywords: Prabu Geusan Ulun museum, educational tourism, history, and culture